The application of expert system to exploration of the robot motion - Ramašauskas, Olegas; Bielskis, Artūras (Lietuvos matematikos rinkinys, 2001)
This article expands robot motion dynamics solutions in the symbolic form and analyses the results with simple newly designed expert system (XPS). The coherency using XPS principles with artificial neural networking methods also discussed. The software implementation in Visual LISP environment examples and knowledge base files are presented.